The effect of tooth age on colour adjustment potential of resin composite restorations. Issue 2 (February 2015) - Tanaka, A.; Nakajima, M.; Seki, N.; Foxton, R.M.; Tagami, J.
Abstract Objectives The purpose of this study was to investigate the effect of tooth age on colour adjustment potential of resin composite restorations in human teeth. Methods Twenty extracted human premolars with an A2 shade, extracted for orthodontic reasons from younger patients (20–28 yrs) (younger teeth) and periodontal reasons from older patients (45–69 yrs) (older teeth), were used in this study. Cylindrical shaped cavities (3.0 mm depth; 2.0 mm diameter) were prepared in the centre of the crowns on the buccal surface. One of four resin composites of A2 shade (Kalore, KA; Solare, SO; Clearfil Majesty, MJ; Beautifil II, BF) was placed in the cavity, and the colour was measured at four areas (0.4 mm × 0.4 mm) on the restored teeth (area 1; tooth area 1.0 mm away from the border of resin composite restoration: area 2; tooth border area 0.3 mm away from margin of resin composite restoration: area 3; resin composite border area 0.3 mm away from margin of resin composite restoration: area 4; resin composite area at the centre of resin composite restoration) using a spectrophotometer (Crystaleye). The colour of each area was determined according to the CIELAB colour scale. Colour differences (ΔE*) between the areas of 1 and 2, 2 and 3, 3 and 4 and 1 and 4 were calculated, and also the ratio of ΔE*area2–3 to ΔE*area1–4 (ΔE*area2–3/1–4), ΔE*area3–4 to ΔE*area1–4 (ΔE*area3–4/1–4) and ΔE*area1–2 to ΔE*area1–4 (ΔE*area1–2/1–4) as a parameter of the colour shift in resin composite restoration, were determined. Moreover, the light transmission characteristics of the resin materials and dentine discs from the younger and older teeth were measured using a goniophotometer. The data were statistically analyzed using two-way ANOVA, and Dunnett's T3 and t-test for the post hoc test. Results ΔE*area2–3 (colour difference between resin composite and tooth at the border) and ΔE*area1–4 (colour difference between resin composite and tooth) of the older teeth groups were significantly larger than those of younger teeth groups (p < 0.05). The ΔE*area2–3/1–4 (mis-match rate in colour shifting at the border) of the older teeth groups was larger than that of the younger teeth groups (p < 0.05). ΔE*area3–4/1–4 (colour shifting rate of resin composite side) was significantly larger in older teeth than younger teeth (p < 0.05), while ΔE*area1–2/1–4 (colour shifting rate of tooth side), was significantly smaller in older teeth than younger teeth (p < 0.05). In each tooth group, there were no significant differences in ΔE*area2–3, ΔE*area1–4, ΔE*area2–3/1–4, ΔE*area3–4/1–4 and ΔE*area1–2/1–4 between the materials (p > 0.05). Analysis of the light transmission properties indicated that older dentine transmitted more light, while younger dentine exhibited greater light diffusion and transmitted less light. Conclusions The colour shifting effects at the border of the resin composite restorations were influenced by the age of the tooth. This behaviour might be influenced by the light transmission characteristics of dentine in restored teeth. Clinical significance The potential for colour adjustment of resin composite restorations may be less in older teeth than younger teeth.